Diagnostic and therapeutic guidelines of dermatitis herpetiformis (Duhring's disease) - consensus of Polish Dermatological Society - Agnieszka Żebrowska; Elżbieta Waszczykowska; Cezary Kowalewski; Katarzyna Woźniak; Małgorzata Olszewska; Waldemar Placek; Rafał Czajkowski; Jacek Szepietowski; Rafał Białynicki-Birula; Marian Dmochowski (Termedia Publishing House, 2016)
Dermatitis herpetiformis (Duhring's disease) is an autoimmune blistering dermatosis with a characteristic polymorphic, itchy rash. The autoimmune process against transglutaminases (TGs) is connected with asymptomatic or with mild symptoms of gluten-sensitive enteropathy (GSE). The diagnostic approach in DH should rely on clinical evaluation, direct immunofluorescence of perilesional skin and evaluation of serum IgA antibodies with ELISA with one substrate of four substrates from which to choose (tTG, eTG, npG, neo-tTG) using the ELISA method. In cases showing an equivocal clinical-laboratory picture such an approach should be broadened by performing histopathology of lesional skin and examining the HLA DQ2/DQ8 haplotype. Combined treatment with dapsone and a gluten-free diet in individualized combinations is generally the therapeutic method of choice in DH.